Anti-Tumor Necrosis Factor Therapies Reduce Serum Macrophage Inflammatory Protein-1? in Ankylosing Spondylitis - Akbulut, Handan; Koca, Suleyman S.; Ozgen, Metin; Isik, Ahmet (J Rheumatol Publ Co, 2010)
[Abstract Not Available]
Keywords: Rheumatoid-Arthritis; Factor-Alpha; Chemokine; Cytokine; Expression; Joints; Cells